The Nexus between Oil and Non-Oil Revenue on Economic Development in Nigeria - Samuel, Ogunbiyi, Sunday; Adedigba, Abina, Praise (International Journal of Economics, Business and Management Studies, 2019)
Revenue generated from oil and non-oil product serves as the main channel trough which the government generate income to service its public goods. The objective of this study is to investigate the role oil and non-oil revenue play in development process in Nigeria. in the stusy economic development was proxied as human development index which served as the dependent variable while oil and non-oil revenue was used as independent variable. The data for the study was gotten from central bank of Nigeria bulletin and index mudi for the period 1981 to 2018. The study made use of Descriptive Statistics, Augmented Dickey-Fuller Unit Root test, Johansen Cointegration and Error Correction Estimates. The error correction estimates result showed that oil revenue has a negative but significant relationship with human development index, the negative contribution arose as a result of the resource curse ideology while non-oil revenue has a positive but insignificant relationship with human development index. Thus, diversification of exportable product is required. There is need to boost security surveillance on the high sea so as to reduce smuggling which will reduce illegal export of crude oil.